Environmental enrichment and the aging brain: is it time for standardization?. (August 2022) - Balietti, Marta; Conti, Fiorenzo
Abstract: Aging entails a progressive decline of cognitive abilities. However, since the brain is endowed with considerable plasticity, adequate stimulation can delay or partially compensate for age-related structural and functional impairment. Environmental enrichment (EE) has been reported to determine a wide range of cerebral changes. Although most findings have been obtained in young and adult animals, research has recently turned to aged individuals. Notably, EE can contribute identifying key lifestyle factors whose change can help extend the "mind-span", i.e., the time an individual lives in a healthy cognitive condition. Here we discuss specific methodological issues that can affect the outcomes of EE interventions applied to aged rodents, summarize the main variables that would need standardization ( e.g., timing and duration, enrichment items, control animals and setting), and offer some suggestions on how this goal may be achieved. Reaching a consensus on EE experiment design would significantly reduce differences between and within laboratories, enable constructive discussions among researchers, and improve data interpretation. Highlights: Adequate stimulation of the aging brain can delay/compensate for age-related impairment. Environmental enrichment (EE) is a promising protocol to extend the "mind-span". We offer some suggestions on the key variables requiring standardization. Consensus on EE experimental design would improve the bench to bedside process.